Mistycyzm żydowski a gnostycyzm w późnej starożytności - Piwowarczyk, Przemysław (Śląskie Studia Historyczno-Teologiczne, 2006)
Gershom Scholem, the founder and main authority of modern research on Jewish mysticism, strictly connected the first ancient stage of this religion phenomenon, so called Hekhalot or Merkavah mysticism, with Gnosticism (in its broad definition). Sholem’s complex view was questioned by some authors of younger generation, however the relations between main ideas of Gnosticism and early Jewish Mysticism have not been yet precisely characterized. In first part of this paper I examine the Jewish milieus from which Gnosticism emerged such as Qumran community, Philo’s Therapeutes, baptistic sects and followers of Simon Magus. Then I compare some main ideas of Hekhalot Mysticism and Gnosticism in order to find dependencies and discrepancies between them. As a result of this analysis it can be stated that there is no common core in Gnostic and Hekhalot tradition. The latter did not possess a fundamental Gnostic opposition between Good Father and Demiurge, divine spark and matter. At first sight there is a delusive similarity in scheme of ascension of the soul but in deeper analysis it cannot be stated any longer. Mutual dependencies are rather minor and they occur especially in the field of magic. If we want to call the esoteric knowledge of Hekhalot mysticism a Gnosis we should stress that it is not a Gnosis of Gnosticism. The aim of these two ways of ascension to the Heaven was definitely different. When the Gnostic practiced a self-salvation, Jewish mystic used his specific Gnosis as means of reaching God’s Throne and God itself – what was for him an ultimate aim.